Prophylactic continuous positive airway pressure after pulmonary lobectomy: a randomized controlled trial - Palleschi, Alessandro; Privitera, Emilia; Lazzeri, Marta; Mariani, Sara; Rosso, Lorenzo; Tosi, Davide; Mendogni, Paolo; Righi, Ilaria; Carrinola, Rosaria; Montoli, Matteo; Reda, Marco; Torre, Massimo; et al. (Journal of Thoracic Disease, 2018)
Background: Despite advances in perioperative care and surgical techniques, patients undergoing pulmonary lobectomy are still at high risk for postoperative complications. Among interventions expected to reduce complications, continuous positive airway pressure (CPAP) is a discussed option. This trial aims to test the hypothesis whether prophylactic application of CPAP following pulmonary lobectomy can reduce postoperative complications. Methods: The study was designed as a prospective, randomized, controlled trial. Patients with clinical stage I non-small cell lung cancer scheduled for pulmonary lobectomy were eligible and were trained for the use of CPAP interface. The control group received standard postoperative pain management and physiotherapy; in addition, the study group received CPAP (PEEP 8–12 cmH2O, 2 hours thrice daily for three days). Results: After the appropriate selection, 163 patients were considered for the analysis: 82 patients constituted the control group, 81 the study group. The two groups were substantially comparable for preoperative parameters. The rate of postoperative complications was lower in the study group (24.7% vs. 43.9%; P=0.015) as well as the hospital stay (6 vs. 7 days; P=0.031). The stepwise logistic regression model identified: CPAP [odd ratio (OR): 0.3026, CI: 0.1389–0.6591], smoke habits [OR: 2.5835, confidence interval (CI): 1.0331–6.4610] and length of surgery in minutes (OR: 1.0102, CI: 1.0042–1.0163) as regressors on postoperative complications. Conclusions: The present trial demonstrated that prophylactic application of CPAP during the postoperative period after pulmonary lobectomy for stage I non-small cell lung cancer was effective in prevent postoperative complications.